2019
DOI: 10.1177/2045894019882623
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of exercise pulmonary hypertension are intermediate between controls and patients with pulmonary arterial hypertension

Abstract: Mechanisms underlying pulmonary arterial hypertension (PAH) remain elusive. Pulmonary arterial hypertension and exercise PH share similar physiologic consequences; it is debated whether they share biologic mechanisms and if exercise PH represents an early phase of pulmonary arterial hypertension. We conducted an observational study to test if there is a graded metabolic disturbance along the severity of PH, which may indicate shared or disparate pathophysiology. Individuals referred to an academic medical dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Moreover, integrated analysis was carried out to explore shared differential metabolites as well as dysregulated metabolic pathways in PAs and the RV. Metabolic reprogramming of PAH has been previously characterized in animal models ,,, and patients. It should be noted that most of these studies were designed to assess the metabolic profile in one particular tissue or sample, such as blood (plasma/serum), the lungs, or the RV tissue. Izquierdo-Garcia et al have used NMR-based metabolomics together with the technique of 18F-FDG PET imaging to characterize the metabolic profile in the heart and lung tissues in a PAH mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, integrated analysis was carried out to explore shared differential metabolites as well as dysregulated metabolic pathways in PAs and the RV. Metabolic reprogramming of PAH has been previously characterized in animal models ,,, and patients. It should be noted that most of these studies were designed to assess the metabolic profile in one particular tissue or sample, such as blood (plasma/serum), the lungs, or the RV tissue. Izquierdo-Garcia et al have used NMR-based metabolomics together with the technique of 18F-FDG PET imaging to characterize the metabolic profile in the heart and lung tissues in a PAH mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The differences of biologic mechanisms between exercise pulmonary hypertension and PAH were analyzed using metabonomics. They found that PAH group presented perturbations in several pathways such as collagen deposition, fatty acid, and glycolysis [ 16 ]. In addition, metabolomic profiles were conducted to differentiate PAH and idiopathic PAH [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] However, before standardised treatment can be initiated, a precise and reliable definition of exPH is needed, since it seems to be a unique pathological entity, with patients displaying different alterations in biochemical pathways than resting PH patients and healthy controls. 12,13 Additionally, the kinetics of hemodynamic recovery seem to vary between different types of PH and exPH. 14 Several factors appear to limit the cardiovascular response to increased right ventricular (RV) afterload during exertion.…”
Section: Introductionmentioning
confidence: 99%